Maquillée - B., Daphné (Éditions Marchand de feuilles, 2020)
Maquillée est le fruit étonnant d'un nombre incalculable d'heures perdues, passées à enchaîner les tutoriels maquillage sur YouTube, ou encore à naviguer sur le site web de Sephora. Cet essai poétique tire profit d'une obsession personnelle, le maquillage, pour développer une réflexion singulière sur notre époque. Se situant au carrefour des discours sur le genre, l'identité, le capitalisme et la culture pop, le maquillage est un objet d'étude riche et complexe, plus que jamais pertinent. S'il est habituellement dédaigné des sphères intellectuelles, Daphné B. nous prouve hors de tout doute qu'il mérite notre attention. Dans un monde oculaire troué de selfies et bouleversé par une industrie de l'influence, Daphné B. propose une réflexion nuancée, féministe et personnelle sur l'univers de la beauté. Objet littéraire hybride, à cheval entre le récit de soi, le poème et l'essai, Maquillée est une méditation lyrique sur un secteur économique en pleine croissance.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; beauté; corps; cours; fem3500; féminisme pop; genre; identités LGBTQIA2+; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Navigating, challenging, and contesting normative gendered discourses surrounding women’s pornography use - Marques, Olga (Journal of Gender Studies, 2019)
While there exists some empirical research on women’s use of pornography, the manner in which women do, and how they understand their pornographic spectatorship, remains under-examined. Focusing on the narratives of 26 women gained through both focus groups and individual interviews, this research explores how women who use pornography and other sexually explicit materials navigate, reaffirm, challenge, and contest normative gendered boundaries that surround women’s sexuality, sexual pleasure, and women’s pornographic use. While ‘pornography as female degradation’ is the most visible feminist discourse, the findings of this study suggest that the meanings attributed to both the experience of engaging with pornography, as well as with pornographic materials themselves, were far from wholly degrading, and in fact, served to provide pleasure, sexual self-actualization, and even corporeal validation – disrupting normative discourses of desiring and desirable bodies.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; corps; cours; féminisme pop; ontario; premier cycle; périodes historiques; régions géographiques; sex1911; sexualité; thématiques

Trente - Darsigny, Marie (Les éditions du remue-ménage, 2018)
Trente, un nombre qui n’arrivera jamais et s’il arrive, je l’éviterai, comme j’ai une fois évité un chevreuil en conduisant sur la route, le chevreuil courait devant mon auto, à gauche il y avait la rivière et à droite il y avait le fossé, c’est beau la Montérégie, au lieu de choisir l’un ou l’autre il continuait d’avancer droit devant, puis il a fini par bondir vers le fossé. Moi j’aurais choisi l’eau et d’ailleurs, à chaque fois que j’empruntais ce chemin-là, ça me chicotait de savoir que juste un petit coup de volant pouvait m’envoyer dans la rivière, un jour on est en vie et un jour on ne l’est plus, c’est tout.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; cours; discours dominant; fem3500; féminisme pop; premier cycle; périodes historiques; québec; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; violences

Filles - Darsigny, Marie (Les éditions de l'écrou, 2017)
Filles, c’est la plainte de celle qui quitte le bar après le last call, celle qui fixe le vide de l’hôpital jusqu’à ce que les murs ondulent, c’est l’idée entêtante que tout ira toujours plus mal, que rien ne sera salutaire, que le fond arrivera plus vite si on gratte le bobo jusqu’à en scrapper sa manucure ; c’est toutes ces petites blessures qui se font facilement et qui cicatrisent mal. ​
Keywords: amériques; approches et analyses; corps; féminisme pop; poésie; québec; régions géographiques; santé; santé mentale; thématiques; violences

Femmes, attitudes performatives: aux lisières de la performance et de la danse - Colloque "Femmes, aux lisières de la performance et de la danse" (2012 : Vandœuvre-lès-Nancy, France), attitudes performatives; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy (Les Presses du réel, 2014)
La place et le rôle des femmes dans l'art et dans le spectacle vivant, entre 1912 et 2012, aux lisières de la performance et de la danse. A l'heure des re-enactements et autres remakes des performances historiques, il semblait important de s'interroger sur la place des femmes dans les avant-gardes des années 1910-1970. Quel regard portons-nous, aujourd'hui, sur les pionnières qui ont profondément modifié la danse et la performance, en Europe et aux Etats-Unis ? Réunis pour la première fois, des historiens, des philosophes, des danseurs et deux chorégraphes ont accepté de faire le point sur leurs recherches. Par-delà les catégories artistiques (danse, performance, action, pantomime, théâtre, music-hall...) et les clivages (théorie / pratique ; forme / fond), ce livre est une invitation à partager leurs questionnements sur le spectacle vivant « au féminin », ses archives et ses références. Femmes, attitudes performatives rassemble dix contributions, une « interview performative » de La Ribot et un entretien sur La Part du rite de Latifa Laâbissi et Isabelle Launay.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes féministes; arts; corps; cours; danse; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire de la danse; performance; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

The Black body in ecstasy: reading race, reading pornography - Nash, Jennifer C. (Duke University Press, 2014)
In The Black Body in Ecstasy, Jennifer C. Nash rewrites black feminism's theory of representation. Her analysis moves beyond black feminism's preoccupation with injury and recovery to consider how racial fictions can create a space of agency and even pleasure for black female subjects. Nash's innovative readings of hardcore pornographic films from the 1970s and 1980s develop a new method of analyzing racialized pornography that focuses on black women's pleasures in blackness: delights in toying with and subverting blackness, moments of racialized excitement, deliberate enactments of hyperbolic blackness, and humorous performances of blackness that poke fun at the fantastical project of race. Drawing on feminist and queer theory, critical race theory, and media studies, Nash creates a new black feminist interpretative practice, one attentive to the messy contradictions—between delight and discomfort, between desire and degradation—at the heart of black pleasures.
Section: x, 219 p. : ill. ; 23 cm.
Keywords: 1900-1999; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; féminisme afroaméricain; féminisme pop; lit4700; pornographie; premier cycle; périodes historiques; queer; régions géographiques; sexualité; thématiques; états-unis; études culturelles

Miss representation (Girls Club Entertainment, 2011)
Like drawing back a curtain to let bright light stream in, MISS REPRESENTATION uncovers a glaring reality we live with every day but fail to see. Written and directed by Jennifer Siebel Newsom, the film exposes how mainstream media contributes to the under-representation of women in positions of power and influence in America. The film challenges the media’s limited and often disparaging portrayals of women and girls, which make it difficult for women to achieve leadership positions and for the average woman to feel powerful herself. In a society where media is the most persuasive force shaping cultural norms, the collective message that our young women and men overwhelmingly receive is that a woman’s value and power lie in her youth, beauty, and sexuality, and not in her capacity as a leader. While women have made great strides in leadership over the past few decades, the United States is still 90th in the world for women in national legislatures, women hold only 3% of clout positions in mainstream media, and 65% of women and girls have disordered eating behaviors.
Place: San Francisco, Calif.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; documentaire; féminisme pop; premier cycle; périodes historiques; représentation des femme*; régions géographiques; santé; sex2283; sexualité; thématiques; travail; états-unis

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Les éditions du remue-ménage, 1983)
Les textes Morgan, R. (1983). La pornographie et le viol : théorie et pratique et Dworkin, A. (1983). Pour les hommes, liberté d’expression. Pour les femmes, silence, s’il vous plaît ont été donné en lecture au corus SEX1911.
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis